Penatalaksanaan Selulitis Praseptal di Praktik Kedokteran Pedesaan: Tantangan dan Keberhasilan Terapi – Laporan Kasus: Laporan Kasus - Ohman, Selvania; Said, George Raden Mas (Cermin Dunia Kedokteran, 2026)
Introduction: Preseptal cellulitis is an infection localized to the anterior portion of the orbital septum. The most common causes are Staphylococcus aureus and Streptococcus species. Beta-lactam antibiotics are considered the first-line treatment. However, rural settings pose challenges due to limited diagnostic resources and widespread antibiotic use without medical supervision. Case: A 29-year-old woman presenting to a rural health center with eyelid swelling and localized pain. The patient had a history of irrational amoxicillin use. Limited access to culture testing and guidelines led to empiric ciprofloxacin therapy. The patient demonstrated significant clinical improvement after five days of treatment. There was no disease progression or complications. Discussion: Amoxicillin-clavulanate and cephalosporin remain the preferred treatments for preseptal cellulitis because they provide appropriate coverage against common gram-positive pathogens. Ciprofloxacin is not routinely recommended as monotherapy because of its variable activity against streptococci, potential adverse effects, and risk of promoting antimicrobial resistance. Nevertheless, previous reports have included ciprofloxacin in alternative regimens for patients with severe beta-lactam allergy or limited therapeutic options. In this case, its use represented a context-specific clinical decision based on prior incomplete antibiotic exposure, medication availability, and the absence of microbiological testing. Careful clinical assessment and close monitoring were essential to ensure treatment safety. Conclusion: This case illustrates the potential use of ciprofloxacin as a pragmatic alternative in resource-limited environments where first-line agents are unavailable.